EFEKTIVITAS MEDIASI DALAM MENYELESAIKAN SENGKETA KONSUMEN DI BPSK KOTA PADANG - Daniel Jusari (Jurnal Public Administration, Business and Rural Develoment Planning, 2019)
Mediation as an alternative dispute resolution is considered to have beneficial forces, mediation can produce win-win solutions for the parties, and mediation is a relatively inexpensive and time-consuming segregation resolution process, dispute resolution through mediation efforts also has been known in the culture of traditional communities in Indonesia for a long time, especially in the Minangkabau community in West Sumatra known by the traditional philosophy of "Bulek aia kapambuluah, bulek kato kamupakaik. Picak salayang, sagolek bulek ". However, these beneficial forces have not been able to make mediation as an effective alternative dispute resolution for consumer dispute resolution in the city of Padang. This research is empirical or sociological in nature with exploratory prescriptive approach. The results of this study explain how the implementation of mediation in the settlement of consumer disputes at BPSK Padang city. The ineffectiveness of mediation efforts in resolving consumer disputes at BPSK is due to several factors ranging from the rules regarding the implementation of mediation, the role of mediators, facilities and infrastructure in the mediation and the attitude of the parties themselves.